Antimicrobial Resistance Threats in the emerging COVID-19 pandemic: Where do we stand? - Soumya Ghosh; Charné Bornman; Mai M. Zafer (Elsevier, 2021)
Antimicrobial resistance (AMR) continues to exert a substantial toll on the global health and world economy and is now expected to be hidden by COVID-19 for a while. The wrong consumption of antibiotics during the COVID-19 pandemic will raise disastrous effects on AMR management and antibiotic stewardship programs. This is related to the concerns extrapolated due to an increase in mortality rates in patients with bacterial coinfections. Importantly, the immune system of COVID-19 patients in regions with high AMR may be fighting on two fronts altogether, the virus and MDR bacteria. Current control policies to manage AMR and prioritization of antibiotic stewardship plans are mandatory during this pandemic. This review aims to discuss the rising concerns of the excess use of antibiotics in COVID-19 patients highlighting the role of bacterial coinfections in these patients. Types of prescribed antibiotics and the development of antibiotic resistance is addressed as well.